Review paperRestoring sinus rhythm in patients at a high risk for postoperative atrial fibrillation - Benussi, Stefano; Galanti, Andrea; Alfieri, Ottavio (Archives of Medical Science, 2008)
The development of atrial fibrillation (AF) is one of the most common occurrences during follow-up after cardiac surgery. AF is a well recognized risk factor for increased postoperative complications and mortality. Preoperative use of antiarrhythmic medications has also been associated with a higher rate of postoperative AF. To enhance postoperative recovery of sinus rhythm in these patients, various perioperative antiarrhythmic drug regimens, including amiodarone, and repeated DC shock cardioversion have been adopted. Despite such strategies, AF tends to re-establish itself after surgery in over 75% of patients, with patients having mitral surgery faring worse than those undergoing aortic valve operations. The development of surgical ablation enables sinus rhythm to be restored in as many as 70% of patients. However, the large scale adoption of such techniques has also raised the issue of post-ablation arrhythmias. Although relapsing atrial fibrillation is generally addressed conservatively, most automatic arrhythmias require electrophysiological assessment and ablation, frequently transseptal. Completeness of the lesion sets and durable transmurality of the ablations are key to preventing most postoperative dysrhythmias.